Relationship between inter-arm blood pressure differences and predicted future cardiovascular risk in hypertensive patients - Faroque, Abu S. M. O.; Das, Prabir K.; Dey, Asish; Hossan, M. Sawkat; Ibrahim, Evana; Latif, Sayem B. (International Journal of Research in Medical Sciences, 2024)
Background: Hypertension stands as a widely recognized significant risk factor for cardiovascular disease. In clinical practice, it is advisable to measure blood pressure (BP) in both arms. The increasing attention on inter-arm blood pressure difference (IABPD) stems from its association with cardiovascular disease. This study aimed to assess the relationship between inter-arm blood pressure differences and predicted future cardiovascular risk in hypertensive patients. Methods: This cross-sectional study was conducted at the department of cardiology, Chittagong Medical College Hospital from July 2020 to June 2021. The study included 428 cases of previously or newly diagnosed hypertension, selected through convenient sampling. Data analysis was conducted using Microsoft Office tools and statistical package for the social sciences (SPSS) version 23.0. Results: In this study, 8.2% of patients exhibited noteworthy systolic IAD, and 2.3% demonstrated notable diastolic IAD. Median 10-year cardiovascular risk, assessed by Framingham and ASCVD calculators, was 21% and 11% respectively. A positive correlation was observed between sIAD and 10-year cardiovascular risk (p=0.003) and sIAD and 10-year ASCVD risk (p=0.041). Patients with significant sIAD had a higher incidence of ischemic heart disease compared to those without (p=0.041). Multiple regression analysis revealed a significant correlation between 10-year Framingham cardiovascular risk and sIAD (p=0.003). Conclusions: A significant difference in systolic blood pressure between arms is linked to a higher 10-year cardiovascular risk and the presence of cardiovascular disease in well-managed hypertensive patients. So, monitoring sIAD could be an additional factor in predicting future cardiovascular events in patients receiving hypertension treatment.